Habituation of Moderate Learning in Islamic Religious Education at Elementary School - Faisal Faisal (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to describe and analyze moderate learning habituation in Islamic Religious Education at a public elementary school in Palembang, along with the challenges and opportunities for its implementation. This research uses a qualitative approach by collecting data through interviews and observations of the Headmaster and Teachers. Data were analyzed using the Miles and Huberman method. This research found that habituation of moderate learning is carried out through preliminary, core, and closing activities in Islamic Religious Education learning. Teachers facilitate discussions and debates, avoiding overemphasis on certain aspects that can lead to extremes in understanding. The use of technology is an opportunity to increase the accessibility and attractiveness of learning. The main challenge lies in the varying levels of religious understanding among students and the limited time and materials for learning. Teachers are trying to overcome this challenge with innovation in learning approaches. The use of technology, support from community organizations, and innovation in learning methods are opportunities to form an inclusive environment that supports moderate learning habituation.